An interesting case of metastatic brain abscess - V, Chandramouleeswaran; V, Kannan; Ranganathan, Lakshmi Narasimhan; S, Balasubramanian; M, Jawahar; A, Nithyanandam (Indian Journal of Case Reports, 2019)
Klebsiella pneumoniae is a Gram-negative, non-motile, lactose fermenting, aerobic rod-shaped bacterium with three different subspecies, K. pneumoniae, Klebsiella ozaenae, and Klebsiella rhinoscleromatis. Here, we report the case of a 32-year-old male, chronic alcoholic presented with fever, hemoptysis, and headache of 20 days duration. Over a period of 4 days, the patient worsened with the development of altered sensorium and respiratory distress, connected to a mechanical ventilator. Computed tomography and chest X-ray showed consolidation involving the left lower lobe with an air-fluid level. Magnetic resonance imaging brain showed multiple metastatic brain abscess involving cerebrum and cerebellum and culture reports of sputum and blood showed K. pneumoniae. The patient was started on antibiotics along with anti-tubercular drugs. In spite of effective management, the patient developed recurrent episodes of hemoptysis and died of respiratory failure. For the concomitant involvement of both cerebrum and cerebellum for the first time.